The Influence Of Transformational Leadership: Accelerating Farmer Group Empowerment To Realize Export-Oriented Agrıbusıness - Roosganda Elizabeth; Giovanni Inez Erika Margaretha; Geraldy Samuel Ivan; Martinus Tukiran (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The role of leadership affects the performance of institutional organizations, companies, business ventures, trade, education, and so on, which aim to be implemented and realized goals, at least exist, develop and even increase. This paper aims to express more comprehensively the relationship between the transformational leadership function of farmer groups partially or simultaneously with the success of an agricultural development program in rural areas, such as PNPM Mandiri, Export-Oriented Agribusiness Progam, P3A etc. The various programs have been more developed performance and objectives in addition to increasing the income and welfare of farmers, the regional economy also aims to realize the development of rural agribusiness aimed at exports. The location and respondent farmer groups were selected purposively, one of which was Hamlet II of Air Merah village, Malin Deman sub-district, Mukomuko Regency, Bengkulu Province, with the Makmur Farmer Group, Sumber Karya, Tani Makmur, Bukit Saroden, 2018-2020, related to the influence of transformational leadership on farmer groups receiving and implementing the program. Quantitative method with descriptive survey from primary and secondary data. Primary data were obtained from interviews and questionnaires with leaders and respondent farmer groups to determine the function of leadership towards farmer group members, as an institution of farmers receiving the program. The results of the study which became a novelty interpreted descriptively qualitative, enriched review of some of the results of studies and related literature, showed: